Novel drug targets for monkeypox: From viral to host proteins - Zhaozhong Zhu; Qin Sun; Yunhai Xu; Youya Niu; Fei Yang; Shuidong Feng (Infectious Medicine)
Background: The ongoing threat of the monkeypox virus (MPXV) underscores the need for new antiviral treatments, yet drug targets and candidate therapies are limited. Methods: Calculating the centrality, conservation, and immunogenicity of MPXV proteins in the network to identify viral drug targets. Constructing the MIP-human protein interaction network and identifying key human proteins as potential drug targets through network topology analysis. Results: We constructed a comprehensive protein–protein interaction (PPI) network between MPXV and humans, using data from the P-HIPSTer database. This network included 113 viral proteins and 2 607 MPXV-interacting human proteins (MIPs). We identified three MPXV proteins (OPG054, OPG084, and OPG190) as key targets for antiviral drugs, as well as 95 critical MIPs (most interacting MIPs, MMIPs) within the MPXV–human PPI network. Further analysis revealed 31 MMIPs as potential targets for broad-spectrum antiviral agents, supported by their involvement in other viral interactions. Functional enrichment of MIPs indicated their roles in infection and immune-related pathways. Conclusions: In total, we identified 112 drugs targeting MPXV proteins and 371 drugs targeting MMIPs, with fostamatinib, trilostane, and raloxifene being able to inhibit both viral and host proteins. This work provides critical insights into MPXV–human interactions and supports the development of targeted antiviral therapies.